2022
DOI: 10.3389/fnut.2022.1027629
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of selenium on metabolism and type 2 diabetes

Abstract: Selenium is recognized as an essential element for human health and enters human body mainly via diet. Selenium is a key constituent in selenoproteins, which exert essential biological functions, including antioxidant and anti-inflammatory effects. Several selenoproteins including glutathione peroxidases, selenoprotein P and selenoprotein S are known to play roles in the regulation of type 2 diabetes. Although there is a close association between certain selenoproteins with glucose metabolism or insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…As largely expected for a nutrient such as selenium and its selenoproteins, such deleterious effects favoring conversion of MCI to dementia would occur only at high concentrations of this selenoprotein, mirroring the more general U-shaped effect of this essential element on human health 7 , 10 . In addition, the growing evidence suggesting an etiologic role of insulin resistance and glucose metabolism abnormalities in the etiology of dementia and specifically of Alzheimer’s disease 38 41 provides biological plausibility for involvement of selenoprotein P in dementia etiology, given the adverse effects on insulin sensitivity and more generally glucose metabolism induced by this selenoprotein 13 , 15 , 37 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…As largely expected for a nutrient such as selenium and its selenoproteins, such deleterious effects favoring conversion of MCI to dementia would occur only at high concentrations of this selenoprotein, mirroring the more general U-shaped effect of this essential element on human health 7 , 10 . In addition, the growing evidence suggesting an etiologic role of insulin resistance and glucose metabolism abnormalities in the etiology of dementia and specifically of Alzheimer’s disease 38 41 provides biological plausibility for involvement of selenoprotein P in dementia etiology, given the adverse effects on insulin sensitivity and more generally glucose metabolism induced by this selenoprotein 13 , 15 , 37 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is part of numerous enzymes, including being a cofactor for glutathione peroxidase, an antioxidative enzyme. Its concentration is considered a factor influencing the frequency of HCC recurrences [ 67 , 68 ]. Metabolically, selenium deficiency results in increased fat accumulation in the liver and intensified insulin resistance [ 69 ].…”
Section: Vitamins and Trace Elements As Supportive Elements In The Pr...mentioning
confidence: 99%
“…Selenium is an essential micronutrient for human health [ 223 ] and is a crucial constituent in selenoproteins, which have diverse biological functions, including anti-inflammation and antioxidation [ 223 ]. Selenoproteins P plays an important role in regulating T2D.…”
Section: Organokines and Dietary Interventionsmentioning
confidence: 99%
“…A study utilizing selenoprotein P-neutralizing antibodies demonstrated that glucose metabolism is significantly improved in high-energy diet-induced mice [ 224 ]. However, low or high selenium supplementation increases insulin resistance by up- or down-regulating selenoproteins in our body, suggesting that moderate intake of selenium is crucial [ 223 , 225 ]. Furthermore, selenium supplementation dramatically improved plasma levels of IGF-1, FGF-21, adiponectin, and leptin levels, protecting against diet-induced obesity in mice [ 226 ].…”
Section: Organokines and Dietary Interventionsmentioning
confidence: 99%